Outdoor Particulate Matter, Cardiovascular Health and Incidence of Coronary or Ischemic Stroke Events: A Population-Based Study (Epidemiology, Biostatistics, and Public Health, 2025)
IntroductionLong-term exposure to outdoor particulate matter of size